FAKTOR YANG MEMENGARUHI KELELAHAN KERJA PADA TENAGA KERJA BONGKAR MUAT (TKBM) DI PELABUHAN BELAWAN - Rupina Kanasia Situmorang (Jurnal Kesehatan dan Fisioterapi, 2022)
The problem of work fatigue in loading and unloading workers, namely fatigue that occurs due to monotony of a job, the frequency and workload of workers, decreased motivation and quality of work. All the things that cause fatigue are united in the body so that it can result in feelings of fatigue for workers. For this reason, it is necessary to take precautions to overcome risks that can make workers experience fatigue. The purpose of this study was to determine the factors that affect work fatigue in loading and unloading workers (TKBM) at the Port of Belawan in 2020.                   The design of this research is descriptive quantitative research with cross sectional design approach. The study used a purposive sampling technique because not all samples had criteria that were in accordance with the phenomenon being studied as many as 51 people. Primary data collection methods, secondary and tertiary data and data analysis techniques used are linear regression correlation test.                   The results showed the variables that had an influence on work fatigue, namely, age and workload and variables that had no effect on work fatigue, namely Body Mass Index and years of service, so it could be concluded that there was an effect of age and workload on work fatigue. The most dominant variable affecting work fatigue is workload                   The conclusion is there is an effect of age on work fatigue on loading and unloading workers (TKBM) at Belawan Port, and there is an effect of workload on work fatigue on loading and unloading workers (TKBM) at Belawan Port.Keywords: Age, Workload, Work Fatigue, TKBM, Belawan Harbor